Izzy, willy-nilly - Voigt, Cynthia (New York : Atheneum Books for Young Readers, 1986)
A car accident causes fifteen-year-old Izzy to lose one leg and face the need to start building a new life as an amputee.
Notable/Best Books (A.L.A.).
School Library Journal.
Wilson's Junior High School.
6.0
7.2
5-8.
Keywords: Amputees -- Fiction; People with disabilities -- Fiction; Physically handicapped -- Fiction